BIOMARKERS OF METHOTREXATE-INDUCED IMMUNE TOLERANCE - ALEXANDRA JOSEPH; JOHNSON TRAN; SUSAN M RICHARDS (2024)
To provide a method of treating a disease such as Pompe disease in a subject.SOLUTION: The method includes: detecting an erythropoiesis biomarker in a sample of a subject following administration of methotrexate and a therapeutic agent to the subject; and administering further treatment, with or without concurrently administering additional immune tolerance induction or immunosuppression therapy on the basis of a level of the erythropoiesis biomarker. Further provided by the present application are methods and kits for assessing the level of immune tolerance to a therapeutic agent in a subject on the basis of the detection of the erythropoiesis biomarker following administration of the methotrexate and therapeutic agent to the subject.SELECTED DRAWING: None 【課題】対象の疾患、例えばポンペ病を処置する方法を提供する。【解決手段】対象へのメトトレキセートおよび治療剤の投与の後に対象の試料の中の赤血球形成バイオマーカーを検出すること、ならびに赤血球形成バイオマーカーのレベルに基づいて、追加の免疫寛容性誘導療法または免疫抑制療法を同時に投与して、または投与しないで、さらなる処置を投与することを含む方法を提供する。対象へのメトトレキセートおよび治療剤の投与の後の赤血球形成バイオマーカーの検出に基づいて、対象における治療剤への免疫寛容性のレベルを調査するための方法およびキットが、本出願によりさらに提供される。【選択図】なし